Design of organizational and economic management mechanism for foreign economic activity of the enterprises - Алексєєва, Тетяна Іванівна (Technology audit and production reserves, 2016)
Development and implementation of organizational and economic mechanism for foreign economic activity of the enterprise at the present stage of market economy development needs to adapt to changing environmental conditions. This is due to the processes of globalization, integration and significant influence of various factors on business outcomes. In this article it is proved an expediency of increasing the export potential of the enterprise, subject to counter the negative effects of the factors influence of external and internal environment. It is revealed that the late adoption of management decisions can lead to loss of competitive position of the enterprises in foreign markets. The technique of carrying out a comprehensive analysis of the foreign economic activity of the enterprise to avoid bankruptcy and improve the efficiency of foreign trade activities is proposed.